Reformasi Pelayanan Kesehatan Primer pada Puskemas Rawat Inap Sukabumi Kota Bandar Lampung - Handrio Pinos; Bambang Utoyo; Devi Yulianti (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2021)
Currently, bureaucratic reform is a necessity for the government apparatus. Reform is carried out as an ongoing effort which at each process or stage is expected to be able to provide changes or improvements for the better. With the implementation of reform, it is hoped that it will be able to realize good governance and be able to bring changes to the delivery of public services that are able to meet the needs of the community. One form of service provided by the government is the fulfillment of public health needs. Health service is a concept carried out by the government to provide health services to the community as one of the basic rights that must be fulfilled. Therefore, this study focuses on looking at how primary health care reform is being carried out by Puskemas inpatient Sukabumi. The research method used is descriptive with a qualitative approach, data collection is done by observation, documentation and interviews. The results showed that the service reform carried out by the Sukabumi inpatient health center has not shown optimal results due to efforts to improve the quality of public services both in terms of service performance evaluation, improvement of service procedure systems, and increasing personnel resources, some improvements still need to be made.